THE EFFECTIVENESS OF E-LEARNING MEDIA IN OPTICAL GEOMETRY ON LEARNING OUTCOMES OF STUDENTS OF SMAN PAKUSARI, CITY OF JEMBER - Mahardika, I Ketut; Subiki, Subiki; Natasha, Dellya; Maula, Muhammad Irham; Kurnia Putri, Widuri (EduFisika: Jurnal Pendidikan Fisika, 2022)
Geometry optics is one of the materials that must be mastered by students, but based on the research results it can be seen that students’ understanding of geometric optics tends to be lacking. This study aims to determine the effectiveness of using e-learning in teaching and learning activities, especially material regarding optical geometry to students of SMA N 1 Pakusari Jember. This study used a field survey method with direct observation in the field. This field survey took place at SMA N 1 Pakusari Jember with the implementation of observations of class XI MIPA 1 students. Based on the acquisition and suitability between learning outcomes from student learning accuracy there is 60% of the accuracy of answer questions which can be said to be quite effective by using e-learning-based learning media. web. While the remaining 40% is less effective when using web-based e-learning learning media. In addition, it can be seen from the results of the hots questions where students get quite high accuracy of answers by looking at the number of correct answers and wrong answers from students. With the acquisition of accuracy of 47% -63% of the answers and the acquisition of correct answers more than the acquisition of wrong answers. So it can be concluded that the use of web-based e-learning learning media on optical geometry material is quite effective